Creating quality precision instrument : VFMA_35 for the conduct of value for money audit using the rasch model / Razimah Abdullah and Mohd Saidfudin Masodi. - Abdullah, Razimah; Masodi, Mohd Saidfudin (Universiti Teknologi MARA Cawangan Selangor, 2012)
Just like an examination paper, the reliability of a survey questionnaire as a measuring instrument is crucial if we want a good and valid instrument. The length of test and rating scale or distractor operational definition are among the determinants that will affect the validity of the instrument. However, how do we assure that we are measuring what is to be measured? This paper investigates the construct validity of an instrument named, VFMA_35 by applying the Rasch analysis. The precision of the instrument is established from the item measurement standard error (SE). Analysis using Rasch creates a functional precise instrument which has the unique predictive ability of measurement and is operable to meet all the requirements of prudent measurement.